Miscarriage Australia: the use of a human centered design approach to design and develop a website for those affected by miscarriage - Bilardi, Jade; Webb, Amy; Trieu, Van-Hau; Sharp, Gemma; McIntosh, Jennifer; Temple-Smith, Meredith (Frontiers in Public Health, 2023)
Background: Past research has shown that Australians affected by miscarriage want a website specific to both miscarriage and their local region that is accessible, comprehensive, evidence-based and informed by experts. The aim of this study was to design, develop and evaluate the Miscarriage Australia website using human centered design. Methods: A four stage human centered design approach was used to develop the Miscarriage Australia website. Results: The design of the website was guided by the research team’s past study findings and interview data. Two user archetypes (personas) were developed from the data which then guided the tone of voice guidelines, branding and website content. Website content was developed by the research team and edited by the designers, before being reviewed by a 13-member Expert Clinical Advisory Committee over two rounds to ensure it was evidence based and reflected best practice. Website prototypes were tested with users who reported positive feedback about the design, branding and appropriateness of website content. Most navigated easily through the website, successfully finding the required information. Minor areas for improvement included slight changes to specific imagery, improved navigational links on section headings, a title change to one section heading for content clarity and additional links to other pages throughout. Conclusion: The Miscarriage Australia website was successfully implemented and commended as meeting users’ needs a result of using human centered design. The Miscarriage Australia website provides an ideal template or blueprint on how to develop a successful and useful digital resource for users, particularly around sensitive women’s health issues.